Will South Africa meet the Sustainable Development Goals target for maternal mortality by 2030? - Y Pillay; J M Moodley (South African Medical Journal)
In September 2015, South Africa (SA) and 192 countries adopted Agenda 2030, which included the Sustainable Development Goals. With a mere 6 years to go before 2030, it is useful to understand what progress SA is making towards their attainment. In this short report, we assess progress towards meeting the maternal mortality target, globally and in SA. The maternal mortality ratio that countries are expected to reach is no more than 70 deaths per 100 000 live births. A range of sources is used to show progress, with an emphasis on the reports of the National Committee on Confidential Enquiries into Maternal deaths, which reports on the number of maternal deaths in health facilities, together with reasons for these deaths and recommendations to reduce preventable mortality.